Ми маємо A (x) = x ^ 2-6x + 4, питання - факторіз A (x) +5?

Ми маємо A (x) = x ^ 2-6x + 4, питання - факторіз A (x) +5?
Anonim

Відповідь:

#A (x) = (x-3) * (x-3) #

Пояснення:

Ми маємо, #A (x) = x ^ 2-6x + 4 #

Тому, #color (білий) (xxx) A (x) + 5 = (x ^ 2-6x + 4) + 5 #

#rArr A (x) = x ^ 2-6x + 9 #

#rArr A (x) = (x) ^ 2 - 2 * x * 3 + (3) ^ 2 #

#rArr A (x) = (x-3) ^ 2 #

#rArr A (x) = (x - 3) (x - 3) #

Зверніть увагу на це

#color (червоний) a ^ 2x ^ 2-bx + c ^ 2 = (sqrt (a ^ 2x ^ 2) -sqrt (c ^ 2)) ^ 2 = (ax-c) ^ 2 # Де #b = 2ac #